(untitled) (Equilibrium: Jurnal Pendidikan, 2025)
Climate-related problems are one of the serious problems that must be faced by various strategic fields, one of which is through the field of education. Environmental ethics-based education is expected to be one of the important strategies that can increase the awareness and responsibility of each individual towards the sustainability of life. The method used in this research is a qualitative method supported by sources of scientific articles, journals, research reports that support and are related to the main topic of discussion. The purpose of writing this article is to be able to explain related to environmental ethics-based education in dealing with climate change so that it can realise justice between generations. The results show that through the cultivation of environmental ethics-based education can form a responsible mindset and behaviour in managing the environment. This requires collaboration from various fields and policy makers who influence decision making in preparing a just life for future generations. In addition, through environmental ethics education, it can create an environmentally conscious generation that is committed to managing the environment so as to support sustainable living. Thus, environmental ethics and environmental justice are interconnected and morally responsible to sustain life for future generations.